Consensus-Based Load Frequency Control of a Multi-Area Power System - Ravi Patel; Chathura Wanigasekara; Akshya Swain; Abhisek Ukil (IEEE Access)
The integration of renewable energy sources into modern power grids presents challenges for load frequency control (LFC) due to the increased system dynamics and uncertainties introduced by variable generation sources. Traditional LFC methods are limited in their ability to handle multi-area, mixed-generation systems where synchronous and asynchronous generators, such as doubly fed induction generator (DFIG)-based wind energy conversion systems (WECS). To address these challenges, this study proposes a multi-agent-based framework using a consensus-based controller strategy to effectively regulate system frequency across a multi-area power network, including conventional and renewable generation sources. The proposed framework divides a large power system network into multiple control areas, each containing various generators. In each area, one generator is selected as an agent, and consensus-based controllers are designed to cooperate across agents, ensuring stable frequency regulation under abnormal conditions such as sudden load changes and faults across the network. The performance of the proposed controller is evaluated using the IEEE 39-bus test system, which includes 10 synchronous generators and 6 wind generators. Simulation results demonstrate that the consensus-based controller achieved up to 30% faster settling times and up to 25% reduction in overshoot during fault conditions, consistently providing a smoother and more stable frequency response. These findings highlight the improved stability and robustness of the proposed control strategy in maintaining system performance across various operating scenarios, demonstrating its superiority in handling the complex dynamics of mixed-generation power systems.